Determination of the optimal cut-off value of serum prostate-specific antigen in the prediction of skeletal metastases on technetium-99m whole-body bone scan by receiver operating characteristic curve analysis - Manohar, P; Rather, Tanveer; Khan, Shoukat (World Journal of Nuclear Medicine, 2020)
Radionuclide whole-body bone scan is a useful investigation of choice to detect the skeletal metastases in prostate cancer. It is indicated in patients having elevated serum prostate-specific antigen (Sr. PSA) or patients with bone pain. Elevated Sr. PSA levels have high predictive value for skeletal metastases; however, there is no consensus regarding cut-off value of Sr. PSA above which bone scan is indicated. This study was performed to find out the accuracy of Sr. PSA test and to know the optimal cut-off value of Sr. PSA with high sensitivity and specificity in the prediction of skeletal metastases on bone scan in prostate cancer patients. A retrospective analysis of medical records of 307 prostate cancer patients referred to the department of nuclear medicine for bone scan between June 2009 and June 2014 was done. Of 307 patients, 15 cases were excluded due to nonavailability of Sr. PSA. Bone scan was performed 3 h after administration of 20 mCi Tc-99m methylene diphosphonate intravenously. Whole-body sweep imaging was performed and spot views were taken wherever required. Of 292 cases, 174 (59.58%) patients had positive bone scan for metastases and 118 (40.41%) patients had negative bone scan for metastases. Maximum and minimum Sr. PSA levels in positive and negative bone scan patients were 1260 and 0.02 ng/ml and 198.34 ng/ml and 0.01 ng/ml, respectively. On comparison of the mean Sr. PSA levels between positive and negative groups, we found significant Sr. PSA levels (P < 0.05). We used receiver operating characteristic (ROC) curve analyses to find out the accuracy of Sr. PSA test and to know the optimal cut-off value of Sr. PSA with maximum sensitivity and specificity in the prediction of skeletal metastases on bone scan. Area under ROC curve was 0.878 (87%). This indicates that the accuracy of Sr. PSA test in the prediction of skeletal metastases on bone scan was good. The optimal cut-off value of Sr. PSA in the prediction of positive bone scan for skeletal metastases in the management of prostate cancer was 29.16 ng/ml, with sensitivity and specificity of 89.0% and 74.6%, respectively. In this study, we conclude that the accuracy of Sr. PSA test in the prediction of skeletal metastases is good. ROC-derived optimal cut-off value of Sr. PSA for positive skeletal metastases on bone scan is >29.16 ng/ml; thus, the chances of getting positive bone scan for skeletal metastasis are less in prostate cancer patients with Sr. PSA <29.16 ng/ml. ROC-derived sensitivity and specificity of different possible cut-off points of Sr. PSA help reduce the false positive results and increase the diagnostic accuracy of bone scan in the detection of skeletal metastases in prostate cancer patients.
Keywords: Prostate cancer; prostate-specific antigen; receiver operating characteristic curve analyses; technetium-99m